The Australian Sports Commission
ASC Mission Statement, 1994: Recognising the immense role sport has to play in providing health, social and economic benefits to the nation, the Australian Government directs its contribution to sport through a single national body - the Australian Sports Commission (ASC). The ASC carries out its task on a national scale with leadership, assistance and funding. The two objectives of the Commission are: - increased participation in sport and sport activities by all Australians - excellence in sports performance by Australians Through a wide variety of programs, the ASC aims to provide opportunities for all Australians.